2020
DOI: 10.1180/mgm.2020.7
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical fingerprints of brannerite (UTi2O6): an integrated study

Abstract: Brannerite (UTi2O6) is among the major uranium-bearing minerals found in ore deposits, however as it has been long considered as a refractory mineral for leaching it is currently disregarded in ore deposits. Brannerite is found in a variety of geological environments with the most common occurrences being hydrothermal and pegmatitic. On the basis of scanning electron microscopy observations coupled with electron probe micro-analyses and laser ablation inductively-coupled plasma mass spectrometer analyses, this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 69 publications
0
10
0
2
Order By: Relevance
“…Natural brannerites are an important U-bearing mineral and have been well-studied with regard to their age and actinide inventories. Microprobe analysis of mineral specimens has shown that they contain significant fractions of other elements including Ca, Pb, Th, Y, and Ln on the U site and Si, Al, and Fe on the Ti site. The family of synthetic brannerites includes the (prototypical) end members CeTi 2 O 6 , UTi 2 O 6 , ThTi 2 O 6 , and PuTi 2 O 6. The nonradioactive Ce-brannerite does not require stringent radioprotection safeguards to handle, and this, combined with the fact that Ce and Pu have very similar crystal chemistry and ionic radii, has led to interest in it as a surrogate material for the Pu-end member (nominally PuTi 2 O 6 ). However, the temperature-dependent nature of the Ce 4+ /Ce 3+ redox couple leads to a difference in chemical behavior when compared to Pu, for example in solubility within glass matrices .…”
Section: Introductionmentioning
confidence: 99%
“…Natural brannerites are an important U-bearing mineral and have been well-studied with regard to their age and actinide inventories. Microprobe analysis of mineral specimens has shown that they contain significant fractions of other elements including Ca, Pb, Th, Y, and Ln on the U site and Si, Al, and Fe on the Ti site. The family of synthetic brannerites includes the (prototypical) end members CeTi 2 O 6 , UTi 2 O 6 , ThTi 2 O 6 , and PuTi 2 O 6. The nonradioactive Ce-brannerite does not require stringent radioprotection safeguards to handle, and this, combined with the fact that Ce and Pu have very similar crystal chemistry and ionic radii, has led to interest in it as a surrogate material for the Pu-end member (nominally PuTi 2 O 6 ). However, the temperature-dependent nature of the Ce 4+ /Ce 3+ redox couple leads to a difference in chemical behavior when compared to Pu, for example in solubility within glass matrices .…”
Section: Introductionmentioning
confidence: 99%
“…Параметры съемки: твердотельный лазер с длиной волны 780 нм, мощность лазера 15 мВт (при 50% мощности), дифракционная решетка 800 линий/мм, время сканирования 10 с, количество сканов 20, спектральный диапазон регистрации 3400-50 см -1 , разрешение 1 см -1 , калибровка проведена по стандартному образцу кремния. За последние годы в связи с возрастающим интересом к ядерному сырью появилось довольно много работ, посвященных рамановской спектроскопии браннерита (Frost et al, 2011, Zhang et al, 2013, Turuani et al, 2020. Набор полос в спектрах зачастую различается как по положению, так и по интенсивностям, что связано, на наш взгляд, во-первых, с тем, что диагностика браннерита без использования рентгеновских методов не является однозначной, поскольку при том же составе минерал может оказаться уранополикразом, во-вторых, на характер спектра оказывает существенное влияние степень метамиктности и интенсивность вторичных изменений минерала.…”
Section: описание браннерита из долины р кукурт на восточном памиреunclassified
“…Низкие содержания свинца (PbO < 0.1 мас.%), слабое замещение браннерита вторичными продуктами говорят с большой вероятностью о молодом возрасте урановой минерализации в долине Кукурта и возможной связи ее с неогеновыми лейкогранитами шатпутского комплекса. Особенности элементного состава браннерита с Памира в свете типохимизма минерала (Turuani et al, 2020) не позволяют сколько-нибудь определенно отнести его к продуктам гидротермального или пегматитового процесса. Есть все основания надеяться, что генезис урановой минерализации с браннеритом (или хотя бы приуроченность браннерита к пегматитам или гидротермалитам) в долине Кукурта будет в обозримое время решен прямым методом -обнаружением в ходе полевых работ коренного проявления браннерита.…”
Section: основные результатыunclassified
“…The high content of uranium makes brannerite an exploitable uranium resource. It contains uranium in a multivalent state due to its origin [ 3 ] and redox reactions are caused by the radioactive decay. Therefore, tetra-, penta- and hexavalent uranium are able to incorporate into the natural and synthetic brannerite [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%